Nomenclature as a social institution of Soviet society (to the discussion in the journal «Sotsiologicheskie issledovaniya») - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2021)
The polemical style of the article is due to the appearance in the sociological literature of ideas that emphasise the enduring nature of the existence of the nomenclature as a class, inherent in both the Soviet and modern Russian state. Also, no less controversial are the ideas that reduce the function of the nomenclature exclusively to a certain mechanism for the nomination of cadres, based on the increased responsibility of party organisations for the ideological and economic policies carried out by economic bodies. The article offers a sociological and cultural-historical explanation of the nature and essence of the nomenclature as a social institution and social group inherent exclusively in the Soviet statе. The author emphasises the concrete-historical nature of this phenomenon, conditioned by the specific ideological, economic, political and social conditions of the Soviet state at the dawn of its formation and formation. The article reveals the main function of the nomenclature as a social institution, the main purpose of which was to implement and develop a new system of relations, principles and ideals of Marxism, embodied in the Soviet project. It is argued that the implementation of this goal was carried out by solving two main tasks: first, the comprehensive development of the productive forces, which was realised through the organisation of a planned economic system and the mobilisation principle of economic construction. Secondly, the preservation of the principles of interaction, the ideals and values of communist ideas, not only as a matter of course, but also, if possible, as a matter of fact. This was carried out through an ideological monopoly, which was based on a certain interpretation of Marxism and a system of agitation and propaganda built on it. The success of the nomenclature in solving these problems is emphasised. However, the article is not an apologetics of the Soviet nomenclature, since it shows the reasons for not only the «rise», but also the «fall» of the nomenclature as a power-management structure of the Soviet society. The main conclusion of the idea presented in the article is to prove the transitory nature of the existence of the nomenclature as a social institution, due to the specific economic, ideological, political and social conditions of the Soviet state, with the fall of which such a social group as nomenclature also went into oblivion. It is argued that in the new Russian state, built on completely different economic and ideological principles, the need for such a social institution has disappeared.